2021
DOI: 10.47456/argumentum.v13i1.32988
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 e sistema prisional no Brasil: crônica de uma pandemia anunciada

Abstract: Desde março do presente ano, o tema da Covid-19 é tratado em diversos aspectos. Todavia o que chama a atenção é a pouca visibilidade dada ao sistema prisional brasileiro e à situação de homens e mulheres presos/as. O presente artigo tem como propósito a publicização dessa situação. Elaborado com base nos dados do Levantamento Nacional de Informações Estatísticas do Sistema Penitenciário Brasileiro e do Grupo de Monitoramento e Fiscalização do Sistema Carcerário, foi possível aferir que a crise sanitária mundia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Such statements are consistent with information from the GMF, published on October 5, 2020, in which it reported that to date 70,519 tests for diagnosis of COVID-19 have been performed on incarcerated persons. Unfortunately, this represents only 9.42% of the prison population in the country (DUARTE, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such statements are consistent with information from the GMF, published on October 5, 2020, in which it reported that to date 70,519 tests for diagnosis of COVID-19 have been performed on incarcerated persons. Unfortunately, this represents only 9.42% of the prison population in the country (DUARTE, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The low visibility given to the Brazilian prison system and the absence of public debates about COVID-19 in this population, even with favorable conditions for the spread of the pathology, people deprived of liberty have rights to the same conditions of prevention and assistance as the rest of the population, as recommended in the Federal Constitution (DUARTE, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation